Illegal fishing in West Africa and EU accountability - Berner,Henrietta (2024)
Exacerbated by climate change and general overfishing, illegal, unreported, and unregulated (IUU) fishing poses a serious threat to marine biodiversity globally. One particularly affected region is West Africa, where coastal States have historically possessed abundant fishing resources within their Exclusive Economic Zones (EEZs) in the Atlantic Ocean. The reliance on industrial-scale fishing, largely driven by foreign fishing fleets, has contributed to col-lapsing fish stocks and the marginalization of local artisanal fisheries. In addi-tion, IUU fishing accounts for approximately 40% of the region’s total catch, underscoring the widespread prevalence and severity of the issue. IUU fish-ing activities involve violations of various legal instruments at different levels and by different actors. This thesis focuses on violations of the United Na-tions Convention on the Law of the Sea (UNCLOS), the primary legal framework governing the law of the sea and binding upon the EU as well as West African states. The EU is one of the world’s largest importers of fishery and aquaculture products, with imports covering 60% of its seafood consumption. Moreover, the EU has longstanding fishery relations with third countries, including West African states, granting access of the EU long distant fleet to their fishing re-sources. Despite EU commitments to sustainable fisheries management, evi-dence suggests that products derived from IUU fishing continue to enter the EU market in strikingly large quantities. Additionally, vessels in the joint EU long-distance fleet have been suspected of engaging in IUU-related activities in West Africa. This is among other things facilitated by inadequate monitor-ing and enforcement of various international and national laws within West African EEZs, as well as by circumvention methods such as malicious reflagging, joint ventures and flags of convenience. Drawing on UNCLOS and ITLOS case law, the primary obligation in preventing IUU fishing in a specific EEZ lies with the coastal State, which must ensure the sustainable exploitation of marine resources within its EEZs. Allegations of widespread IUU activities in the EEZs of West African coastal States have prompted various EU measures to combat IUU fishing and pre-vent its entry into the EU market. A key feature of the external dimension of the EU’s Common Fisheries Policy is the carding scheme, established through the EU IUU Regulation. This framework allows the European Com-mission to identify third States that do not sufficiently cooperate in combating IUU fishing, meaning notably not living up to its obligations under UNCLOS as coastal, flag or port States. For example, Sierra Leone has been under a yellow card warning since 2016, Liberia since 2017, Ghana since 2021 and most recently Senegal since May 2024, reflecting EU concerns of widespread IUU related activities within these States’ EEZs and inadequate monitoring and enforcement. However, the carding scheme has shown limited substantive impact, primarily restricting new Sustainable Fisheries Partnership Agree-ments (SFPAs) negotiations while not preventing private agreements between individual EU vessels and the carded State, nor the continued importation of fishery products from the concerned EEZ. Except for in relation Cameroon, the EU has refrained from imposing actual trade restrictions due to IUU fish-ing in West Africa, which also is a feature of the IUU Regulation. Trade re-strictions, if applied, would impose bans on fish imports from the concerned coastal State’s EEZ, and moreover directly prohibit EU vessels from operating therewithin. As noted, the obligation to prevent IUU-fishing in a given EEZ largely falls on the coastal State, thus in the context of this theses on West African states. The obligations of the EU in its capacity notably as flag and port State are hence secondary to those of West African states. The flexibility of certain provisions of the Draft Articles on the Responsibility of International Organi-zations (DARIO), particularly the interpretative and debated scope of Article 14 on aid and assistance in the commission of an internationally wrongful act by another state, allows for new legal paths for addressing accountability for the failure of West African states to comply with its UNCLOS obligations related to sustainable fisheries. This thesis suggests that EU actions related to IUU fishing in West Africa amount to aid and assistance to violations of international law committed by West African States, in their failure to ensure compliance with UNCLOS in their EEZs. The actions to be consider aid and assistance of the EU, consid-ered their overall impact, include permitting the import of fish at high risk of being caught through IUU fishing, issuing licenses for fleet operations in wa-ters deemed inadequately monitored and controlled, financially supporting third States that are failing to live up to its obligations under UNCLOS, as well as allowing EU industrial fishing through the maintenance of fisheries agreements and an arbitrary application of its carding scheme based on eco-nomic interest in the West African region. However, due to the uncertainty surrounding the legal status of DARIO and the lack of clarity on the precise scope of international responsibility deriving from aid and assistance, the assessments in this thesis remain largely prelimi-nary and exploratory. The primary intention is to provoke academic discus-sion and provide a foundation for further research on EU accountability for ongoing UNCLOS violations related to IUU fishing in West Africa.
Keywords: Public International Law; the Law of the Sea; International responsibility of International Organizations; DARIO; EU fisheries policy; IUU fishing in West Africa.